The Partition’s Shadow: Unpacking Trauma in Cracking India - Bhattarai, Krishna Prasad; Bhusal, Tilak (Rupantaran: A Multidisciplinary Journal, 2025)
The main objective of this research paper is to explore partition trauma in Bapsi Sidhwa's Cracking India. By portraying a disabled child, Lenny, as a witness, Sidhwa seems to take the Pakistani Muslim's side. The treatment of partition trauma in this novel is biased. This novel unethically portrays the Hindu, Muslim, and Sikh relationship, so it is culturally guided. Rather than normalizing the Hindu –Muslim wound, Sidhwa presents this relationship from the Pakistani perspective, which reminds the partition trauma and leads to post-traumatic stress disorder. This issue is framed within the theoretical parameter of trauma theory, taking the ideas of Avishai Margalit, Caruth, and Pandey.